1987
DOI: 10.1073/pnas.84.16.5535
|View full text |Cite
|
Sign up to set email alerts
|

Lactose permease of Escherichia coli: properties of mutants defective in substrate translocation.

Abstract: ABSTRACT-Mutants of lactose permease of Escherichia coli with amino acid changes (Gly-24 -> Glu; Gly-24 --Arg; Pro-28 --Ser; Gly-24, Pro-28 -> Glu-Ser and Gly-24, -> Arg-Ser) within a putative membrane-spanning a-helix 12 24(Phe-Gly-Leu-Phe-Phe-Phe-Phe-Tyr-Phe-Phe-Ile-Met-GlyAla-Tyr-Phe-Pro-Phe-Phe-Pro-Ile) are incorporated into the cytoplasmic membrane. The mutant proteins retain the ability to bind galactosides, and the affinity for several substrates is actually increased. However, the rate of active trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
15
1

Year Published

1989
1989
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
6
15
1
Order By: Relevance
“…The present studies show that insertion of 6-histidine residues between Tyr-2 and Tyr-3 does not diminish IIA glc binding. In contrast, a lac permease mutant (Thr-7-Ile, Met-11-Ile) does not exhibit IIA glc binding (12,14). It should be noted that Met-11 is located in transmembrane helix I; modification of this residue might result in a change in helix packing and consequently loss of IIA glc binding.…”
Section: Some 6-his Insertion Mutants Of Lac Permease Are Defective Imentioning
confidence: 94%
See 1 more Smart Citation
“…The present studies show that insertion of 6-histidine residues between Tyr-2 and Tyr-3 does not diminish IIA glc binding. In contrast, a lac permease mutant (Thr-7-Ile, Met-11-Ile) does not exhibit IIA glc binding (12,14). It should be noted that Met-11 is located in transmembrane helix I; modification of this residue might result in a change in helix packing and consequently loss of IIA glc binding.…”
Section: Some 6-his Insertion Mutants Of Lac Permease Are Defective Imentioning
confidence: 94%
“…Although a lac permease triple mutant in the N-terminal tail was reported to lack IIA glc binding (14), it has been suggested (15,16) that the allosteric regulation of lac permease is mediated mainly by an interaction of IIA glc with the central cytoplasmic loop.…”
mentioning
confidence: 99%
“…Mutations in putative Helix I of the Lacy protein have been analyzed with respect to the ability of the mutant proteins to bind and translocate galactosides [284]. The mutants G24E and P28S bind normal amounts of NPG with K~ pp values somewhat lower than that of wild-type LacY, but transport with less than 5% the wild-type activity.…”
Section: Vii-d Other Residuesmentioning
confidence: 99%
“…Not only influx but also efflux down a concentration gradient and exchange are greatly reduced. From these data and the accessibility of the galactoside binding site in rightside-out and inside out membrane vesicles, it is concluded that the mutations affect the isomerization of the ternary carrier-substrate-proton (CSH) complex [284]. Recent studies in which varying numbers of amino acids have been deleted from the aminoterminus of LacY have indicated that the first 22 amino acids, corresponding with the N-terminal half of the first putative transmembrane a-helix are not essential for transport [154].…”
Section: Vii-d Other Residuesmentioning
confidence: 99%
“…Nelson et al (14) and Overath et al (17) described a lactose permease triple mutant defective in its N terminus (carrying a T-to-I mutation at position 7 [T7I], M11I, and G24R) and a partial revertant (T7I and M11I), which were reported to lack IIA Glc binding. These results suggested that the N-terminal 11 residues of LacY might be involved in IIA Glc binding.…”
mentioning
confidence: 99%